Daily 10 mg rivaroxaban as a therapy for ventricular thrombus related to left ventricular non-compaction cardiomyopathy: A case report. Issue 4 (January 2018) - Sun, Huan; Zhao, Qini; Wang, Yanjing; Lakin, Robert; Feng, Haiyan; Fan, Xingyu; Luo, Huiling; Gao, Dongmei; Liu, Lin; He, Yuquan; Yang, Ping
Abstract: Rationale: Left ventricular non-compaction cardiomyopathy (LVNC) is a rare heart disorder related to thrombosis. Anticoagulant therapy is suggested for the treatment of this disease. The success of the novel oral anticoagulant rivaroxaban as a treatment option for this disorder is unclear. Patient concerns: A 43-year-old man who felt dizzy at rest was found to have an intraventricular thrombus. Diagnoses: The thrombus was confirmed by echocardiography. And LVNC was diagnosed by cardiac magnetic resonance (CMR) and echocardiography. Interventions: He was prescribed a low dose (10 mg daily) of rivaroxaban as treatment. Outcomes: After 3 months, the thrombus diminished, and the manifestation disappeared. Lessons: Low dose of rivaroxaban may serve as a viable option for anticoagulation therapy in LVNC patients, with large clinical trials needed to determine the best course of treatment. Abstract : Supplemental Digital Content is available in the text